Question
upstudy study bank question image url

Solve the polynomial equation \[ 4 x^{3}+x^{2}-36 x-9=0 \]

Ask by Stewart Mcdonald. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \(x=-3\), \(x=-\frac{1}{4}\), and \(x=3\).

Solution

Solve the equation \( 4x^{3}+x^{2}-36x-9=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(4x^{3}+x^{2}-36x-9=0\) - step1: Factor the expression: \(\left(x-3\right)\left(x+3\right)\left(4x+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-3=0\\&x+3=0\\&4x+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=3\\&x=-3\\&x=-\frac{1}{4}\end{align}\) - step4: Rewrite: \(x_{1}=-3,x_{2}=-\frac{1}{4},x_{3}=3\) The solutions to the polynomial equation \(4x^{3}+x^{2}-36x-9=0\) are \(x=-3\), \(x=-\frac{1}{4}\), and \(x=3\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the polynomial equation \( 4x^{3}+x^{2}-36x-9=0 \), we can apply the Rational Root Theorem, synthetic division, or the method of finding roots using numerical techniques. However, for this case, let’s first look for rational roots by testing possible factors of the constant term (-9) and the leading coefficient (4). The possible rational roots can be given by ± factors of -9 divided by ± factors of 4: Possible rational roots: \( \pm 1, \pm 3, \pm 9, \pm \frac{1}{2}, \pm \frac{3}{2}, \pm \frac{9}{4} \). Let's start testing some of these values: 1. Testing \( x = 3 \): \[ 4(3)^3 + (3)^2 - 36(3) - 9 = 4(27) + 9 - 108 - 9 = 108 + 9 - 108 - 9 = 0 \] So, \( x = 3 \) is a root. Now we can perform synthetic division of the polynomial by \( x - 3 \). Performing synthetic division: \[ \begin{array}{r|rrrr} 3 & 4 & 1 & -36 & -9 \\ & & 12 & 39 & 9 \\ \hline & 4 & 13 & 3 & 0 \\ \end{array} \] This gives us a quotient of \( 4x^2 + 13x + 3 \). Next, we can factor or use the quadratic formula to solve \( 4x^2 + 13x + 3 = 0 \). Using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-13 \pm \sqrt{13^2 - 4(4)(3)}}{2(4)} = \frac{-13 \pm \sqrt{169 - 48}}{8} = \frac{-13 \pm \sqrt{121}}{8} \] Calculating further: \[ \sqrt{121} = 11 \] Thus, we have: \[ x = \frac{-13 + 11}{8} = \frac{-2}{8} = -\frac{1}{4} \quad \text{and} \quad x = \frac{-13 - 11}{8} = \frac{-24}{8} = -3 \] Hence, the solutions to the polynomial equation \( 4x^3 + x^2 - 36x - 9 = 0 \) are: \[ x = 3, \quad x = -\frac{1}{4}, \quad x = -3 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy